Real-Time PCR-based detection of bovine DNA by specific targeting on cytochrome-B - Nina Salamah; Yuny Erwanto; Sudibyo Martono; Abdul Rohman (Universitas Ahmad Dahlan, 2019)
The design of specific primers is an interesting research topic such that it offers selective, specific, and effective DNA analysis using real-time PCR. This research was intended to detect bovine DNA using real-time PCR and specific primers to ensure the halal authenticity of food products. Primers of bovine DNA sequences were designed in the NCBI and Primer-BLAST programs. The outcome validation was assessed using several parameters, namely specificity, repeatability, and linearity by real-time PCR. Primer specificity test was performed on fresh tissue (pork and negative control), while the repeatability test used six replications and was based on the calculated coefficient of variation (CV). In the linearity test, six different DNA concentrations (50000, 10000, 5000, 500, 100, and 50 pg/µL) were examined to obtain the efficiency value. Using the specific primer from Cytochrome-B, the real-time PCR could specifically identify the presence of bovine DNA at the optimum annealing temperature of 58.70C. The repeatability analysis yielded a coefficient of variation (CV) of 0.57 %, while the linearity test produced an efficiency value of 206 %. These figures confirm that the method employed in this study is not only specific but also sensitive and reliable for detecting bovine DNA. Real-time PCR using specific primer targeting on the cytochrome-B region of bovine DNA (forward: CTACTGACACTCACATGAATTGG; reverse CACTAGGATGAGGAGAAAGTATAGG) can be used to identify bovine DNA and distinguish it from porcine DNA.